The development of spatial and memory circuits in the rat. Issue 3 (12th December 2016) - Tan, Hui Min; Wills, Thomas Joseph; Cacucci, Francesca
Abstract : We provide a concise review of recent studies related to the development of neural circuits supporting spatial navigation and memory in the rat. We chart the relative timeline of the emergence of the four main classes of spatially tuned neurons within the hippocampus and related limbic areas: head direction cells emerge earliest (postnatal day 12, P12), before the eyes of the rats are even open, followed by place cells and boundary responsive cells; grid cells emerge last, around the age of weaning (P21). The rate of maturation is unique to each type of neuron, with the head direction and grid cells showing rapid developmental spurts, in contrast to place cells, which show a more gradual trend of maturation. Interestingly, the emergence of allocentric spatial abilities occurs only after the full complement of spatial neurons becomes functional at P20–21, whereas associative processing in the place cell network is evident from as early as P16. We also present evidence supporting the view that the sensory inputs, which are particularly salient to adult spatial networks, may not be essential for the immature spatial system. Crucially, visual information, although more salient than other sensory modalities for anchoring the adult head direction system, does not appear to be essential for setting up the immature head direction network. We conclude by highlighting an urgent need for new theoretical models that can account for the sequential emergence of spatial cells, as well as the lack of primacy of vision in the early organization of the head direction network. WIREs Cogn Sci 2017, 8:e1424. doi: 10.1002/wcs.1424 This article is categorized under: Neuroscience > Behavior Neuroscience > Development Neuroscience > Physiology Abstract : Spatial cell types each have a distinct developmental timeline that precede the emergence of spatial memory in the rat